Macroeconomics; theory and policy - Campagna, Anthony S. (Boston : Houghton Mifflin, 1974)
This book is primarily on intermediate macroeconomic theory. The book is intended to provides students with some awareness in the field of macroeconomics without unnecessary complexity.
Includes index
Bibliography: p. 455-459
ucj 17/01/2019
Loans
Keywords: Macroeconomics